Položaj in vloga predsednika Republike Slovenije - Cerar, Miro (Teorija in praksa, 1997)
In Slovenia the President of the Republic is directly elected. Although this is an element of the (semi)presidental system, the constitutional arrangments as a whole prove that Slovenia has a parliamentary system where the focus of political decision that Slovenia has a parliamentary-making lies with the parliament and the government. Since the President has mainly representative, protocolar and iniciative powers, his political role is relatively week. However, through his public appearance and different informal activities, the President can gain significant authority and strong influence in the political arena. The first presidential elections were held only five years ago, which means that only future developments can actually show the real limits of the influence of the President of the Republic. This developments will also prove whether the position and powers of the president are adequately regulated by the new constitution.
Keywords: predsednik republike; parlamentarni sistem; skupščinski sistem; vlada; državni zbor; National Assembly; Slovenia; Slovenija